1981
DOI: 10.1063/1.441313
|View full text |Cite
|
Sign up to set email alerts
|

On the argon–methane interaction from scattering data

Abstract: The Ar-HCl potential energy surface from a global map-facilitated inversion of state-to-state rotationally resolved differential scattering cross sections and rovibrational spectral dataThe rotational and vibrational dynamics of argon-methane. II. Experiment and comparison with theoryThe rotational and vibrational dynamics of argon-methane. I. A theoretical study J. Chem. Phys. 110, 5639 (1999); 10.1063/1.478462Neon-methane and argon-methane isotropic interaction potentials from total differential cross sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0

Year Published

1982
1982
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 42 publications
4
21
0
Order By: Relevance
“…We compare the results obtained from the asymptotically scaled and the non-scaled SAPT potentials with the experimental data from Ref. 4.…”
Section: Introductionmentioning
confidence: 83%
See 4 more Smart Citations
“…We compare the results obtained from the asymptotically scaled and the non-scaled SAPT potentials with the experimental data from Ref. 4.…”
Section: Introductionmentioning
confidence: 83%
“…4. Total differential cross sections for Ar-CH 4 were also measured at slightly different collision energies. 6 Liuti et al 7 reported total integral cross sections for rare gas-methane scattering as functions of the velocity.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations